RESEARCH AND ANALYSIS OF STORAGE WAREHOUSES OF AGRICULTURAL PRODUCTS (Conferencea, 2023)
This article will talk about the study and analysis of storage warehouses of agricultural products, modern storage facilities, storage methods for seed-grain products, fruit vegetables, refrigerated storage facilities